(3cTa GdVHGHI aj eSCdI GdGSJfGHIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai hbY GdSDGd cKjQkG Yf eSCdI GdESJfGHI ai GdhXGFa s
(3BNQgG (B:s
(3afLQi ChbGage Ydi gPG , hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1491s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs